2012
DOI: 10.1037/a0025823
|View full text |Cite
|
Sign up to set email alerts
|

Individual prediction of dyslexia by single versus multiple deficit models.

Abstract: The overall goals of this study were to test single vs. multiple cognitive deficit models of dyslexia (reading disability) at the level of individual cases and to determine the clinical utility of these models for prediction and diagnosis of dyslexia. To accomplish these goals, we tested five cognitive models of dyslexia: two single-deficit models, two multiple-deficit models, and one hybrid model in two large population-based samples, one cross-sectional (Colorado Learning Disability Research Center—CLDRC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
191
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(239 citation statements)
references
References 27 publications
23
191
0
6
Order By: Relevance
“…It has been demonstrated that many predictors should be considered for an accurate diagnosis of SLD (Pennington et al, 2012). There is also an abundance of evidence indicating that a deficit in the basic cognitive processes can predict response to intervention (Al Otaiba & Fuchs, 2002;Frijters et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that many predictors should be considered for an accurate diagnosis of SLD (Pennington et al, 2012). There is also an abundance of evidence indicating that a deficit in the basic cognitive processes can predict response to intervention (Al Otaiba & Fuchs, 2002;Frijters et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Findings that dyslexia is a complex disorder, associated to heterogeneous defi cits, which may lead to diffi culties in reading and in other neuropsychological functions serves as a basis for the multiple defi cit model of dyslexia, which proposes a multivaried continuous performance characterized by cognitive abilities relating to reading (Menghini et al, 2010;Pennington, 2006;Pennington et al, 2012). These theories post that individual differences found in reading and writing are conceptualized in terms of a multidimensional model, where there is a continuous variation of language components and literacy abilities (Bishop & Snowling, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate susceptibility genes have been found to be linked to developmental dyslexia (Galaburda, LoTurco, Ramus, Fitch, & Rosen, 2006;Giraud & Ramus, 2012;Scerri & Schulte-Körne, 2010), and the idea of multiple risk factors, some of which are transmitted also to offspring without dyslexia, is widely accepted (Bishop, 2009;Pennington, 2006;Pennington & Lefly, 2001;Pennington et al, 2012;Snowling, 2008;Snowling et al, 2003). Pennington (2006) has suggested that multiple risk factors both in the genome and environments lead to a continuum of vulnerability instead of a dichotomous distribution of risk.…”
Section: Familial Risk As a Continuummentioning
confidence: 99%